KUANTIFIKATOR DALAM NOVEL MISS PEREGRINE’S HOME FOR PECULIAR CHILDREN KARYA RANSOM RIGGS - Minipko, Marthinus Kamayap (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2013)
This research entitled “Quantifier in the Novel Miss Peregrine's Home for Peculiar Children by Ransom Riggs is written to fulfill the requirement of finishing S1 degree in English Department Faculty of Letters Sam Ratulangi University. The aims of this research are to identify, classify and analyze the quantifiers that exist in the novel Miss Peregrine's Home for Peculiar Children written by Ransom Riggs in terms of function, category and form. In analyzing the data the writer uses descriptive method and the concept of Flor Aarts and Jan Aarts about English Syntactic Structure: Function and Categories in Sentence Analysis. In the novel Miss Peregrine’s Home for Peculiar Children, it is found that there are three forms of the quantifier , they are simple, compound and complex ones. From the functional point of view, the quantifier in this novel has several functions. In the sentence or clause level, the quantifier functions as Subject, Subject Attribute, Predicator Compliment, Direct Object, Indirect Object and Adverbial. In the phrase level, the quantifier can only function as the head of noun phrase, both as the head of noun phrase and determiner, and as determiner only. It also can function as post modifier of noun phrase. Here are some examples of the quantifier in English : someone, somebody, something, anyone, anybody, everyone, everybody, no one, none, some, any, each, all, both, either, few, little, every and no and so on. ____________________________________ Keywords : Functions, Category, Forms, Novel, Miss Peregrine's Home for Peculiar Children.